Designing benzothiadiazole based highly efficient non-fullerene acceptor molecules for organic solar cells. (3rd January 2022) - Afzal, Qaba Qusain; Jaffar, Kinza; Ans, Muhammad; Rafique, Javeria; Iqbal, Javed; Shehzad, Rao Aqil; Mahr, Muhammad Shabir
Abstract: This research is carried out to investigate photovoltaic characteristics of the six modified molecules derived from benzothiadiazole core-based reference molecule JY5, using four different non-fullerene acceptors at ωB97XD/6-31G** via TD-DFT approach. To check the efficiency of these designed molecules dipole moment, band gap, binding energy, chemical-potential, soft and hard character, electrophilicity, light harvesting efficiency, open circuit voltage and fill factor are studied along with transition density matrix, molecular electro-potential surface, density of states and photoinduced electron transfer (PET). Amidst JY5-W1 to JY5-W6 structures, JY5-W4 molecule shows a broad absorption range with a λ max of 458 nm. JY5-W3 and JY5-W4 molecules shows the highest electron mobilities. The outstanding light harvesting efficiencies (>0.90) make the designed molecules a good candidate for organic solar cells. HOMO-LUMO gaps parameterize Voc as a key factor in evaluating photovoltaic outcome of designed molecules (electrophilic in nature) so, PTB7-Th is considered as a preferred donor as its lower HOMO (−5.01 eV) and higher LUMO level (−2.60 eV) results in increased Voc predicting an efficient organic solar cell. Graphical abstract: Image 1 Highlights: Six small molecule acceptors having benzothiadiazole core unit have been designed for photovoltaic applications. The entitled structures demonstrated improved absorption-coefficient in DCM solvent than that of the reference molecule. The novel devised molecules have better absorption, narrow band gap and formidable charge mobility.